2017
DOI: 10.1002/pc.24334
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional carbon nanotube–nanofiber composite foam for selective adsorption of oils and organic liquids

Abstract: Carbon nanotubes (CNTs) have attracted tremendous research interest area as promising sorbent material due to the large surface area for adsorption, excellent mechanical and chemical properties. To practically employ CNTs as a potential commercial sorbent, it is essential to form loosely packed architecture of CNTs in 3D space. In recent years, a series of CNTs‐based composites have been fabricated. However, these composites showed a highly compact structure and/or junctions with uneven/excessive CNTs depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…have various impact on the adsorption of oil on the surface of CNTs [26]. Among the factors, large surface area can be one of the major factors to increase the adsorption capacities of CNT-based surface structures, for which Jin et al [37] demonstrated excellent adsorption capacities of three-dimensional flower-like CNTs-nanofibers foams to selectively adsorb oils and organic liquids. Therefore, the optimal combination of MWCNTs loading and EO coating could achieve the goal to completely remove bacterial cells from aqueous solutions and completely inactivate the cells retained on the filters.…”
Section: Resultsmentioning
confidence: 99%
“…have various impact on the adsorption of oil on the surface of CNTs [26]. Among the factors, large surface area can be one of the major factors to increase the adsorption capacities of CNT-based surface structures, for which Jin et al [37] demonstrated excellent adsorption capacities of three-dimensional flower-like CNTs-nanofibers foams to selectively adsorb oils and organic liquids. Therefore, the optimal combination of MWCNTs loading and EO coating could achieve the goal to completely remove bacterial cells from aqueous solutions and completely inactivate the cells retained on the filters.…”
Section: Resultsmentioning
confidence: 99%
“…Nanofiber membranes attract the most attention among researchers because of their high specific area and porosities that allow them to capture more metal ions on their free sites [ 10 , 11 , 12 , 13 ]. The electrospinning method is able to produce different compositions of electrospun nanofibers with enormous surface areas, high porosity, and gas permeability [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibers membranes attracts more attention among other adsorbents due to high specific area and porosities that allow nanofibers membranes to capture more metal ions on its free sites [10][11][12][13]. Electrospining method has the ability to produces different compositions of electrospun nanofibers with enormous surface area, high porosity and gas permeability [14,15].…”
Section: Introductionmentioning
confidence: 99%